Engineered polymeric nanoparticles of Efavirenz: Dissolution enhancement through particle size reduction. (22nd November 2016) - Vedha Hari, B.N.; Lu, Cui-Lin; Narayanan, N.; Wang, Rui-Rui; Zheng, Yong-Tang
Abstract: Solubility and bioavailability of drug molecules are the key factors influencing their therapeutic effectiveness in-vivo. The desired drug concentration in systemic circulation can be achieved through the required dissolution of the drug in the biological environment which ultimately affects the pharmacological response. Efavirenz is an anti-HIV molecule with low solubility and variable bioavailability (<45%) and prescribed as first line drug with 800 mg dose. The objective of the study was to develop polymeric nanoparticles of Efavirenz and assess the dissolution enhancement, safety and efficacy using T-lymphatic cell lines infected with HIV-1IIIB strain. The nanoparticle formulations were developed using solvent evaporation method and characterized for its size (110–283 nm), charge (−21 to −33 mV), % entrapment efficiency (57–95%), viscosity of nanosuspension (2.39–4.2 cP) and surface area of the particles (1.4 m 2 /g). The fourier transform infrared analysis and differential scanning calorimetry analysis of the pure drug and nanoparticles revealed the compatibility and stability of drug in nanoparticles. The in-vitro dissolution studies of the nanoparticles in distilled water media using type-1 USP dissolution apparatus at 100 rpm showed improved drug release based on the polymer composition, as compared with marketed formulations (capsules). The cytotoxicity and therapeutic activity of nanoparticles was studied by MTT assay in C8166 cell lines and syncytium formation assay using HIV-1IIIB strain infected cell lines, respectively. Cell uptake of the nanoparticles was studied by confocal microscopy. The formulated nanoparticles were found to be safe and exhibiting 2-fold increase in therapeutic activity compared to pure drug, which could be attributed to improved dissolution and high cell uptake. Graphical abstract: Highlights: Efavirenz loaded polymeric nanoparticle developed with small size and high drug loading. Dissolution enhancement through improved surface area. Safety and efficacy was assessed using T- Lymphatic cell line (C8166). Transmission electron and confocal microscopic study reveals spherical particle with better cell uptake.